WONG SALOH SAW PIN OF MASTER ARUNSILP DAUNGMOON - ชมสูง, รัฐสินธุ์; เผ่าสวัสดิ์, พรประพิตร์ (Community and Social Development Journal, 2018)
The research on The Saloh Saw Pin of master Arunsilp Daungmoon is a qualitative research. This research focuses on the study of: 1) Biography master Arunsilp Daungmoon 2) The melodies music and singing of master Arunsilp Daungmoon in Nan province. The data collected by using the Anthropology of Music Methodology from the documents, the interview and participatory observation. Data analysis and presentation of descriptive analysis. The results were shown that Master Arunsilp Daungmoon received the Thai Wisdom Scholar Award from the Ministry of Culture in 2005. The Saloh Saw Pin ensemble of Master Arunsilp shares four common traits of musical cultures in Nan province which include (1) instrumentation of Pin and Saloh; (2) performances beginning with the melodies entitled dad nan; (3) Saloh with frets; and (4) Fon ngan dancing. The analysis of five melodies including of Dadnan, Lablaeng, Panfai, Bhamar Tatongteng, and Pralorderndong reveals the employment of three Penta Centric modes Nine methods of Pin performing techniques, four methods in fiddling Saloh, and six techniques of saw conclude the artistic wisdom of Master Arunsilp who is determined to continue the spirit of Nan melodies.